2000
DOI: 10.2166/wst.2000.0100
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulphide dispersion modelling - urban and rural case studies

Abstract: Sewage treatment works are subject to a range of parameters governing the quality of effluent and sludge produced. An additional product from treatment plants is odorous air. The causes, source, formation and measurement of odour are widely reported and reasonably understood. An important factor in the design and management of works is the prediction of such odours. The importance of this work is explained by the possibility of future legislation controlling odour at wastewater plants. Odour dispersion modelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…The primary concern about these sulfur compounds in WWTPs is their irritating nature, which would cause a nuisance to people in the surrounding neighborhood. Many studies about the malodorants in offgases from WWTPs typically focus on hydrogen sulfide (H 2 S) ( Al‐Shammiri, 2004 ; Parsons et al, 2000 ; Stuetz et al, 1999 ), partly because of a relatively large share of hydrogen sulfide in odorous sulfur‐containing compounds. However, hydrogen sulfide seemed not to be a good marker measuring odor concentrations, although it also had a low odor threshold based on dynamic dilution olfactometry ( Cheng et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…The primary concern about these sulfur compounds in WWTPs is their irritating nature, which would cause a nuisance to people in the surrounding neighborhood. Many studies about the malodorants in offgases from WWTPs typically focus on hydrogen sulfide (H 2 S) ( Al‐Shammiri, 2004 ; Parsons et al, 2000 ; Stuetz et al, 1999 ), partly because of a relatively large share of hydrogen sulfide in odorous sulfur‐containing compounds. However, hydrogen sulfide seemed not to be a good marker measuring odor concentrations, although it also had a low odor threshold based on dynamic dilution olfactometry ( Cheng et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the available surface area for gas transfer is believed to affect the emission of H 2 S from open surfaces to the atmosphere. This was also proved by Parsons et al 20 whom found that the greater open surface area of the source the greater H 2 S concentration emitted to atmosphere. Figure 5 shows the concentration of H 2 S (ppm) emitted to atmosphere from each unit.…”
Section: Resultsmentioning
confidence: 55%
“…This was also proved by Parsons et al . 20 whom found that the greater open surface area of the source the greater H 2 S concentration emitted to atmosphere.…”
Section: Resultsmentioning
confidence: 99%
“…Odour emission can be experimentally determined by laboratory simulations (Cohen et al, 1978;Mackay and Yeun, 1983), by micro-meteorological methods (Rege and Tock, 1996;Parsons et al, 2000), and by gas phase direct sampling (Bliss et al, 1995;Jiang et al, 1995;Jiang and Kaye, 1996). However, owing to their simplicity and low cost involved, empirical mathematical equations are usually used to estimate odour emissions.…”
Section: Introductionmentioning
confidence: 99%